Legal Aspects of the Construction of the Liang Patane Cemetery in North Toraja - Tumbo, Asher; Bima Muttaqin, Elfran (Jurusan Ilmu Hukum Fakultas Syariah dan Hukum uin alauddin, 2025)
Abstract: Legal Aspects of the Patane Cemetery Development which are made such as a house building made of wood or in the form of a permanent building, as a building either made of wood or permanently made on land owned by Tongkonan or privately owned land in terms of permitting, what are the rules that must be met in its construction according to national law, as well as how the customary law rules in the construction of the Liang Patane cemetery. The research method used in this study is the Empirical Juridical Law research method using historical, legal and sociological approaches. Data processing by collecting all data, both primary and secondary data, is then presented with a qualitative descriptive analysis method. The results of the study show that in terms of positive law, both National law and Regional Regulation, there is no rule that regulates knowing this in the National Law which is regulated only the provision of land for cemeteries, North Toraja Regional Regulations There is no regulation on this matter either in spatial planning regulations or regulations related to buildings. In terms of customary law, the construction of the Liang Patane Cemetery is regulated by various aspects ranging from the development plan for the placement of the Development Site and its work, apart from the development side of customary law also provides protection for the building itself which protects from destruction and theft as well as activities around the cemetery. Keywords: Patane Cemetery, Legal Aspects, Customary Law